Pengaruh Penambahan Puree Buah Naga Merah (Hylocereus Polyhizus) Terhadap Karakteristik Jaja Laklak - Ariyani, Putu Eka Putri; Antarini, Anak Agung Nanak; Tamam, Badrut (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2024)
Jaja Laklak has white characteristics but there are also green and pink colors where the dyes used are derived from natural dyes. It has a round shape, served sprinkled with grated coconut and doused with liquid brown sugar solution. The purpose of this study was to determine the characteristics of jaja laklak with additionsPuree red dragon fruit. The research method used, the experimental method used a randomized block design (RBD) with 5 treatments and 3 replications. The results of the subjective analysis of jaja laklak including color, aroma, taste, texture, overall acceptance, color quality, taste quality and texture quality are significant. The results of the objective analysis are fiber content and antioxidant capacity. Data analysis used the ANOVA test if there was a difference in the treatment then it would be followed by the least significant test (LSD). The results showed that there was an added effectPuree red dragon fruit on organoleptic quality including color, texture, taste, overall acceptability, fiber content and antioxidant capacity. AdditionPuree Red dragon fruit as much as 30% produced the most preferred quality with the characteristics of purplish red color, chewy texture, sweet taste, overall acceptance of likes, fiber content of 3.8784% and antioxidant capacity of 7.8900%. Keywords: Jaja Laklak, Addition of Red Dragon Fruit Puree, Fiber, Antioxidant Capacity.